Impact of a Professional Nutrition Program on a Female Cross Country Collegiate Athlete: A Case Report - Majid Mufaqam Syed-Abdul; Dhwani Satishkumar Soni; Jason Daniel Wagganer (MDPI AG, 2018)
Low caloric intake or excessive energy expenditure can lead to a negative energy balance, which, in female athletes, may result in a condition called the female athlete triad. While several guidelines identified proper nutrition as a first line of treatment, little research has been reported to show the effect of a professional nutrition program (PNP) on the female athlete triad. The purpose of this case report was to measure the short- and long-term effects of a PNP on a female athlete presenting triad characteristics. A 20-year-old female track-and-field athlete at a Division I university who was in negative energy balance and amenorrheic underwent a one-month PNP. Short- and long-term effects measured by a dual X-ray absorptiometry scan prior to and after attending a PNP showed increased total energy intake from 2188 kcals to 3187 kcals, which resulted in an increase in body fat percent (BF%) from 4.7% to 6.7%. However, by the end of four months, energy intake and BF% (5.7% and 6.0%) values were reduced, respectively. After the twelve-month follow-up, BF% was increased (10.5%), suggesting that increasing energy intake to meet energy demands, without compromising athletic training, can be an effective treatment for the female athlete triad.